Model of Administration of Local Administration Organization for the Development of Life Quality of the Ageing in LopBuri Province - Te Khan Mak, Kanda; Teh Khan Mak, Kasak; Anantanachai, Panya (Journal of MCU Social Science Review, 2016)
Amanda Lehning, and Annie Harmon. Livable Community Indicators for Sustainable Aging. Stanford Center on Longevity. New York. 2013.Malholtra, Naresh K. Marketing Research : an Applied Orientation. (6th ed.). English, Book, Illustrated edition. 2010. Wan He, Daniel Goodkind, and Paul Kowa. An Aging World: 2015 International Population Reports. U.S. Government Publishing Office, Washington, DC. 2016.